History of art in Japan - Tsuji, Nobuo, 1932- (Columbia University Press, 2019)
"In this book the leading authority on Japanese art history tells the fascinating story of the country's exceptional cultural heritage. Tsuji Nobuo sheds light on how Japan has nurtured distinctive aesthetics, prominent artists, and movements that have achieved global influence and popularity. The History of Art in Japan discusses works ranging from the Jōmon period to contemporary art, from earthenware figurines in 13,000 BCE to manga, anime, and modern subcultures"--